2017
DOI: 10.15361/1984-5529.2017v45n2p182-189
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação foliar de aminoácidos como suplemento à adubação nitrogenada em cultivares de trigo

Abstract: ResumoO manejo da adubação nitrogenada é complexo e dependente das condições edafoclimáticas. A incorporação de aminoácidos via foliar pode suplementar o fornecimento de Nem em determinados estádios de desenvolvimento da planta. O objetivo foi estudar os efeitos da aplicação foliar tardia de aminoácidos nas características agronô-micas e no desempenho produtivo de cultivares de trigo. O experimento foi conduzido em Londrina-PR, sob delineamento experimental de blocos ao acaso, em parcelas subdivididas, em esqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In addition to environmental factors, nitrogen fertilization influences the quality of the wheat, because the W, TP, and the relationship between the tenacity and extensibility can change (CAZETTA et al, 2008). However, the efficiency of the application of urea, the main source of N, depends on the occurrence of suitable climatic conditions, mainly rainfall (GAZOLA et al, 2017). Varga and Svecnjak (2006) reported that the application of N in the form of urea close to anthesis causes a reduction in W. Equally, excess nitrogen fertilization (above 300 kg ha -1 of N) reduces the proportion of high molecular weight glutenins (YUE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental factors, nitrogen fertilization influences the quality of the wheat, because the W, TP, and the relationship between the tenacity and extensibility can change (CAZETTA et al, 2008). However, the efficiency of the application of urea, the main source of N, depends on the occurrence of suitable climatic conditions, mainly rainfall (GAZOLA et al, 2017). Varga and Svecnjak (2006) reported that the application of N in the form of urea close to anthesis causes a reduction in W. Equally, excess nitrogen fertilization (above 300 kg ha -1 of N) reduces the proportion of high molecular weight glutenins (YUE et al, 2007).…”
Section: Introductionmentioning
confidence: 99%